IDENTIFYING LEARNING AND TEACHING MODELS ACCORDING TO DRIYARKARA - Winarti, Eny (Widya Dharma: Jurnal Kependidikan, 2016)
Driyarkara is recognized as an important person for his contribution to education. He is known to be one of the founders of Sanata Dharma University and was the first rector. He is also considered to be the first modern Indonesian philosopher. Unfortunately, despite his contribution, not many people know much about him. In Sanata Dharma, his name is often mentioned, but few people discuss his philosophy and contributions. For this reason, this study was intended to identifY Driyarkara's models for education and the manifestation of his thought in his teaching. To fulfill this purpose, document studies were implemented. The results of the study revealed that he was the follower of progressive education. His thought was also reflected not only in his teaching, but also in his relation with the people in education field around him who were.